2019
DOI: 10.1002/ejoc.201801861
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diazanorcaradienes and 1,2‐Diazepines via the Tandem [4+2]‐Cycloaddition/Retro‐[4+2]‐Cycloaddition Reaction between Methoxycarbonylcyclopropenes and Dimethoxycarbonyltetrazine

Abstract: The reaction of di(methoxycarbonyl)tetrazine with substituted cycloprop‐2‐ene‐1‐carboxylates gives a series of 3,4‐diazanorcaradienes and 1,2‐diazepines. The influence of the nature of cyclopropenes and the reaction conditions on its selectivity was investigated. The addition of nucleophiles to norcaradienes was studied and a rare example of the “walk” rearrangement in this class of compounds was revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Additionally, certain derivatives of cyclopropene have been reported to undergo trimerization under ambient conditions. 43 In all cases a mixture of tautomeric cycloheptatrienes formed in the reaction and individual isomers of 9a and 9c were separated. Based on the literature procedure for the synthesis of diphenyldi(methoxycarbonyl)cyclopentadienone 44 we applied conditions therefrom to the generation of 1 in the synthesis of 9b and improved the yield from 12 to 27% with a prevalence of the symmetrical isomer which was isolated.…”
Section: Paper Synthesismentioning
confidence: 93%
See 1 more Smart Citation
“…Additionally, certain derivatives of cyclopropene have been reported to undergo trimerization under ambient conditions. 43 In all cases a mixture of tautomeric cycloheptatrienes formed in the reaction and individual isomers of 9a and 9c were separated. Based on the literature procedure for the synthesis of diphenyldi(methoxycarbonyl)cyclopentadienone 44 we applied conditions therefrom to the generation of 1 in the synthesis of 9b and improved the yield from 12 to 27% with a prevalence of the symmetrical isomer which was isolated.…”
Section: Paper Synthesismentioning
confidence: 93%
“…It is noteworthy, that the thermal decarbonylation of cyclopentadienone dimers has been reported previously. 43 Therefore, we suggest that the more steric hindrance in dihydroindenone 6 compared to 1 is responsible for the unsuccessful reaction of 4 with the cyclopropene derivative (Scheme 1). On the contrary, according to quantum chemical calculations the addition of methyl diphenylcyclopropenecarboxylate to cyclopentadienone 1 to form tricyclic 8 (Scheme 2) demonstrates a lower barrier than that of the dimerization process (18.7 Previously, 27 Halton et al investigated the elimination of CO from tricyclooctenones similar to 7 and observed endo-isomers to react much faster than exo-isomers.…”
Section: Template For Synthesis Thiemementioning
confidence: 93%
“…11 H -Benzo[4,5]imidazo[1,2- a ]indol-11-one was obtained from 1 H -benzo[ d ]imidazole and 2-fluorobenzaldehyde, according to a known method [ 37 ]. Cyclopropenes 1a [ 41 ], 1b , c [ 42 ], 1d [ 43 ], 1e [ 44 ], 1f , g [ 45 ], and 1h [ 46 ] were prepared according to the literature data, while α-amino acids 3 were obtained from commercial sources. Maleimides 7e [ 47 ] and 7f [ 48 ] were synthesized according to previously described procedures, 7a−d were obtained from commercial sources.…”
Section: Methodsmentioning
confidence: 99%